If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = 2y + -1 Reorder the terms: 12 + 2x = 2y + -1 Reorder the terms: 12 + 2x = -1 + 2y Solving 12 + 2x = -1 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = -1 + -12 + 2y Combine like terms: 12 + -12 = 0 0 + 2x = -1 + -12 + 2y 2x = -1 + -12 + 2y Combine like terms: -1 + -12 = -13 2x = -13 + 2y Divide each side by '2'. x = -6.5 + y Simplifying x = -6.5 + y
| b^2+7b+6=-6 | | xy3/x | | -0.9-1.49n=2.151 | | 2(2x+1)=17 | | y^2/3-25/64=0 | | 2.1(6x/3-4.7)=8.66 | | 3a^2=-16+16a | | 11m+4(m-3)+6m=4m-12 | | [y+2]=3 | | 2/300 | | 6x^2-21x-18= | | 0=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | f(x)=(x-2)(x-i)(x+i)(x-1-i)(x+1+i) | | 2.1(6x/3-4.7)=20 | | 192/6 | | 2(-1-3)(-1-3)(-1-3)-5= | | 87/3 | | 8+16p=16p+8 | | (4cos^2(x)-2)(3cos^2(x))=0 | | 1x*20x=0 | | 4x^2+y^2+4y=0 | | -6y+10=6y+26 | | T=2π√(l/9) | | 6S=228 | | -3x/2 | | (z-1)(2z-7)=0 | | 7+12x=163 | | 3xb+2a+1=-4 | | 7+12x=160 | | -5=-7/y-4 | | Fg(0)= | | 5h+25=3h+30.76 |